Egypt Development Strategy 2030 and the Importance of Partnership with Russia - V. Belov; M. I. M. ElSergani (Informaciâ i Innovacii)
The article considers the main priorities for the development of the Arab Republic of Egypt in the context of the implementation of the Strategy-2030 and the challenges of project implementation of large-scale international initiatives in Afro-Eurasia. The focus of the study is aimed at identifying the potential of the socio-economic aspect of the strategic partnership between Egypt and Russia in accordance with the needs of sustainable national development in the 21st century. The tasks of forming a new architecture of economic cooperation in the context of the deployment of development and security projects determines the relevance and scientific novelty of the issues underlying this work.